Participants at the 1986 y-Walk finish line - Unknown:::Creator::::::::::::
Negative shows a group of men and women walking under the finish line banner for the 1986 y-Walk. The banner reads: "Finish. Avia. High performance athletic footwear." There is another large group of people milling around the entrance to the building and a couple of people at some tables in the parking lot on the right side of the picture. Many of the participants are carrying balloons